Optimization of CRISPR/Cas9 genome editing in cotton by improved sgRNA expression - Lu Long; Dan-Dan Guo; Wei Gao; Wen-Wen Yang; Li-Pan Hou; Xiao-Nan Ma; Yu-Chen Miao; Jose Ramon Botella; Chun-Peng Song (Plant Methods, 2018)
Abstract Background When developing CRISPR/Cas9 systems for crops, it is crucial to invest time characterizing the genome editing efficiency of the CRISPR/Cas9 cassettes, especially if the transformation system is difficult or time-consuming. Cotton is an important crop for the production of fiber, oil, and biofuel. However, the cotton stable transformation is usually performed using Agrobacterium tumefaciens taking between 8 and 12 months to generate T0 plants. Furthermore, cotton is a heterotetraploid and targeted mutagenesis is considered to be difficult as many genes are duplicated in this complex genome. The application of CRISPR/Cas9 in cotton is severely hampered by the long and technically challenging genetic transformation process, making it imperative to maximize its efficiency. Results In this study, we provide a new system to evaluate and validate the efficiency of CRISPR/Cas9 cassettes in cotton using a transient expression system. By using this system, we could select the most effective CRISPR/Cas9 cassettes before the stable transformation. We have also optimized the existing cotton CRISPR/Cas9 system to achieve vastly improved mutagenesis efficiency by incorporating an endogenous GhU6 promoter that increases sgRNA expression levels over the Arabidopsis AtU6-29 promoter. The 300 bp GhU6.3 promoter was cloned and validated using the transient expression system. When sgRNAs were expressed under the control of the GhU6.3 promoter in CRISPR/Cas9 cassettes, expression levels were 6–7 times higher than those provided by the AtU6-29 promoter and CRISPR/Cas9-mediated mutation efficiency was improved 4–6 times. Conclusions This study provides essential improvements to maximize CRISPR/Cas9-mediated mutation efficiency by reducing risk and workload for the application of CRISPR/Cas9 approaches in the targeted mutagenesis of cotton.